SISTEM INFORMASI GEOGRAFIS PERSEBARAN MASYARAKAT MISKIN DI KOTA PALANGKA RAYA - Seprianto Seprianto; Abertun Sagit Sahay; Rony Teguh (Universitas Palangka Raya, 2022)
The Palangka Raya City as Capital of Central Kalimanta, has the secondlowest of amount poor people (3.75%) after Sukamara (3.73%) (CentralKalimantan BPS, 2017).In desig and build the system use the Simple Additive Weight (SAW)method as a decision support system and apply in GeographicInformation System to the visualization of data. In this researchmethodology using systematic implementation process to illustrate,calculate and evaluate data. In this reserch use the methodology throughseveral stages, likely research design, database design, interface design,coding and system testing.The Testing of this system use Blackbox test system. The results of testwith the Blackbox system indicate the system create to runningaccording to the researcher expectation.